O Eu Sou (Egõ Eimí) do IV evangelho e seu enraizamento na tradição bíblica da autarrevelação do Nome Divino. - Gomes, Vando Marques (2023)
The present research has as its object of study the I Am (Egō eimí) of the Fourth Gospel, pronounced several times by Jesus in the Johannine work, and its roots in the biblical tradition of the self-revelation of the divine name. The objective is to reflect on the meaning of this I Am for the IV Gospel in its three forms of occurrence: the simple, the absolute and the accompanied by predicatives; in addition to deepening the Old Testament antecedents that inspired the author of the Gospel in the self-declarations I Am of Jesus and its parallel with the self-proclamations of YHWH, when he also pronounces the I Am. The methodology used was essentially that of bibliographical research. As for the results achieved, it first appears that the I Am of Jesus is a formula of revelation like the I Am of the Old Testament and is part of the tradition of divine self-revelation that permeates all of Scripture. Secondly, this I Am of Jesus finds its roots in the self-presentation of YHWH in Ex 3,14b, as 'ĕhǝyeh, but mainly in the self-proclamations 'ănî hû' of the literature of Deutero-Isaiah, which emphasize the uniqueness of the true God . The third important notion is that this 'ănî hû' of the prophetic literature became so strong that the rabbinical traditions proclaimed the name of God with a version that particularly emphasized the intimacy and solidarity between YHWH and Israel: it was the 'ănî wehû' (I and he). This version was taken up by the author of the Fourth Gospel to show the unity and solidarity between Jesus and the Father. Fourthly, the I am of the IV Gospel is at the service of Christology and the soteriological proclamation that the evangelist wanted to emphasize, in addition to showing who Jesus is in relation to humanity and what he offers in his mission as an envoy of the Father when the I am it is joined to several predicates unique to it. Finally, for the evangelist, Jesus and YHWH are not two gods, but the Father and the Son in full intimacy. Thus, everything that belongs to the Father is given to the Son, including his sacred name; so he can make it fully known to all entrusted to him.